Overexpression of long noncoding RNA 4933425B07Rik leads to renal hypoplasia by inactivating Wnt/β-catenin signaling pathway - Xue, Shanshan; Du, Xuanjin; Yu, Minghui; Ju, Haixin; Tan, Lihong; Li, Yaxin; Liu, Jialu; Wang, Chunyan; Wu, Xiaohui; Xu, Hong; Shen, Qian (Frontiers in Cell and Developmental Biology, 2023)
Congenital anomalies of the kidney and urinary tract (CAKUT) is a general term for a class of diseases that are mostly caused by intrauterine genetic development limitation. Without timely intervention, certain children with CAKUT may experience progressive decompensation and a rapid decline in renal function, which will ultimately result in end-stage renal disease. At present, a comprehensive understanding of the pathogenic signaling events of CAKUT is lacking. The role of long noncoding RNAs (lncRNAs) in renal development and disease have recently received much interest. In previous research, we discovered that mice overexpressing the lncRNA 4933425B07Rik (Rik) showed a range of CAKUT phenotypes, primarily renal hypoplasia. The current study investigated the molecular basis of renal hypoplasia caused by Rik overexpression. We first used Rapid Amplification of cDNA ends (RACE) to obtain the full-length sequence of Rik in Rik+/+;Hoxb7 mice. Mouse proximal renal tubule epithelial cells (MPTCs) line with Rik overexpression was constructed using lentiviral methods, and mouse metanephric mesenchyme cell line (MK3) with Rik knockout was then constructed by the CRISPR‒Cas9 method. We performed RNA-seq on the Rik-overexpressing cell line to explore possible differentially expressed molecules and pathways. mRNA expression was confirmed by qRT‒PCR. Reduced levels of Wnt10b, Fzd8, and β-catenin were observed when Rik was expressed robustly. On the other hand, these genes were more highly expressed when Rik was knocked out. These results imply that overabundance of Rik might inhibit the Wnt/β-catenin signaling pathway, which may result in renal hypoplasia. In general, such research might help shed light on CAKUT causes and processes and offer guidance for creating new prophylactic and therapeutic strategies.